2011
DOI: 10.1111/j.1365-2796.2011.02405.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression alterations at baseline and following moderate exercise in patients with Chronic Fatigue Syndrome and Fibromyalgia Syndrome

Abstract: Objectives To determine mRNA expression differences in genes involved in signaling and modulating sensory fatigue, and muscle pain in patients with Chronic Fatigue Syndrome (CFS) and Fibromyalgia Syndrome (FM) at baseline, and following moderate exercise. Design Forty eight Patients with CFS-only, or CFS with comorbid FM, 18 Patients with FM that did not meet criteria for CFS, and 49 healthy Controls underwent moderate exercise (25 minutes at 70% maximum age predicted heart-rate). Visual-analogue measures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
153
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(161 citation statements)
references
References 57 publications
4
153
1
1
Order By: Relevance
“…These findings contrast with those of previous studies 35,36 in which similar dosages and plasma concentrations of clonidine had a significant and dosedependent effect on blood pressure and heart rate. A potential plasma-expanding effect of clonidine might offset blood 48 of abnormal α 2 -receptor protein transcription in CFS. Alteration of pharmacodynamics might also explain the association between high clonidine concentration and insomnia problems in the present study despite the well-known sedative effect of clonidine and the lack of clonidine's effect on working memory.…”
Section: Hemodynamicsmentioning
confidence: 97%
“…These findings contrast with those of previous studies 35,36 in which similar dosages and plasma concentrations of clonidine had a significant and dosedependent effect on blood pressure and heart rate. A potential plasma-expanding effect of clonidine might offset blood 48 of abnormal α 2 -receptor protein transcription in CFS. Alteration of pharmacodynamics might also explain the association between high clonidine concentration and insomnia problems in the present study despite the well-known sedative effect of clonidine and the lack of clonidine's effect on working memory.…”
Section: Hemodynamicsmentioning
confidence: 97%
“…Hormonelle forstyrrelser er påvist, spesielt for stressfysiologiske mekanismer som involverer HPA-aksen (hypothalamus -hypofyse -binyrebark-aksen) (33,34) . Undersøkelser av pasienter med CFS/ME før og etter fysisk anstrengelse, kan tyde på at de har en endret genregulering etter belastning i forhold til friske (35,36) .…”
Section: Utløsende Faktorerunclassified
“…Despite showing a strong familial aggregation [8][9][10], attempts to identify genetic factors associated with FM (primarily through polymorphism 2 Nursing Research and Practice association studies) have yielded inconsistent results, with some investigators showing associations between FM and specific genes (including, but not limited to, genes for catechol-O-methyltransferase [11][12][13], serotonin-2A receptor [14,15], serotonin transporter gene regulatory region [16,17], dopamine D4 receptor [18], -2 adrenergic receptor [19], gamma-aminobutyric acid receptor subunit beta-3, trace amine-associated receptor 1, interferon-induced guanylatebinding protein 1, regulator of G protein signaling 4, cannabinoid receptor type 1, and glutamate receptor 4 [20]), while others failed to identify a relationship [21][22][23][24][25]. Since a consistent, straightforward association with a gene (s) has not yet been forthcoming, scientists have suggested that the familial influence on FM may more likely reflect a genetic susceptibility to environmental events [21,26,27]. For example, Klengel and Binder [28] identified differential methylation for a glucocorticoid response element (the FKBP5 gene) that resulted from the presence of both an "at-risk" allele (polymorphism) and the occurrence of childhood trauma in subjects they studied who had posttraumatic stress disorder.…”
Section: Introductionmentioning
confidence: 99%